General Intelligence and Socioeconomic Status as Strong Predictors of Student Performance in Latin American Schools: Evidence From PISA Items - Flores-Mendoza, Carmen; Ardila, Ruben; Gallegos, Miguel; Reategui-Colareta, Norma (Frontiers in Education, 2021)
Numerous technical-scientific reports have demonstrated that school performance variability is linked to several factors, especially socioeconomic factors. For a century, differential psychology has shown that students' socioeconomic level has little or no relevance in the explanation of school performance variation when the intellectual factor is considered. Here we present a study on student samples (N = 1264) aged 13 to 16 yrs, enrolled in 32 schools from five Latin American countries (Argentina, Brazil, Chile, Colombia, and Peru). A short version of the PISA test and five cognitive measures were administered, in addition to a socioeconomic questionnaire. Multilevel analysis (marginal models) indicated that intelligence and socioeconomic school status were robust predictors, and students' socioeconomic status does not significantly account for the PISA variation. This study concludes that education policy must incorporate individual differences in intelligence as an important variable in school performance studies.